Municipios e gestao florestal na Amazonia: introducao e marco teorico - Toni, F.; Kaimowitz, D. (A.S. Editores, 2003)
In this chapter, the authors discuss the history of decentralization in Brazil, analyze the institutional and legal characteristics of the Brazilian political system concerning decentralization and build a theoretical framework for the case studies. Brazil has experienced cycles of centralization and decentralization since its independency, in 1822. The 1988 constitution sparked a strong and sustained cycle of decentralization. The country has a strong federal system, in which municipalities get a fair share of federal taxes and already are able to control education and health policies and services. Decentralization in the forest and environment sectors still lag behind. Municipal governments do not have interest in controlling and taxing the forest sector for political reasons and due to the very nature of the fiscal federalism. Yet, in spite of the slow advances and lack of a formal decentralization program, the Brazilian Constitution and laws grant state and municipal governments enough power to take action in these sectors. Municipalities can restrict land use and create protected areas in their territories. However, local governments in Amazonia do not frequently use this and other prerogatives.